Securitization of Syrian Refugees in 2015: A Comparative Analysis between the EU and Turkey - Kama, Anwar (Al-HIKMAH Journal, 2018)
This paper attempts to examine the way in which the European Union (EU) and Turkey dealt with the Syrian refugees in 2015 by employing a securitization framework pioneered by the Copenhagen School. It is argued that while the EU and some of its member states managed to securitize Syrian refugees in 2015-2016 in order to protect the Schengen Zone, Turkey, on the other hands, desecuritized the issue by framing Syrians as a guest in a humanitarian discourse. However, Turkish securitizing actors practically implemented securitization, as a result of the EU influence, through a number of measures in order to control the border. The paper, therefore, seeks to compare and contrast the EU and Turkey’s ways of dealing with Syrian refugee crisis and find out whether different pattern of securitization matters for their positive and sustainable relationship. In doing so, it takes context, actor, securitizing move, policy output, and audience as points of comparison. The study unveils that their securitization undertakings that had been seen as discordant in many layers contributed to the volatility and unusual development of Turkey-EU relations in 2015-2016. Turkey did not and is unlikely to utilize the securitization policy until unless the refugee crisis moves beyond humanitarian limits and becomes connected to terrorism. Thus, humanitarian-based organizations should question the 2016 Turkey-EU deal and advocate the EU to prefer an open door policy instead of its securitization. At the same time, they should also urge Turkey to facilitate safety for the refugees that are heading for their destinations instead of implementing destructive containment policy.